Phenomenological research on professsional knowledge and educational relationship building - Martín-Alonso, Diego; Blanco-García, Nieves (My University, 2018)
Following Dewey’s (1997) and Schwab’s (2013) ideas, Clandinin & Connelly (1992) developed their notion of teacher as curriculum maker, it means, the “teacher not so much as a maker of curriculum but as a part of it and to imagine a place for contexts, culture (Dewey´s notion of interaction), and temporality (both past and future contained in Dewey´s notion of continuity)” (p.365). In this way, teachers are not seen as implementers of curricular plans but as part of the curriculum making process. In other words, they understand that students create their curriculum in their experience at school when they interact with teachers and the environment. Therefore, the educational relationship creates the framework where learning can take place and students can build knowledge (Atkinson, 2015); it means, relationships generate meeting places that allow the making and reshaping of curriculum. If teaching takes place in the relationship, it means recognition (and acceptance) of the other person, of the otherness. It supposes trying to come into relation with the other, and it implies also acceptance of the uncertainty that otherness has. Therefore, education Is not about the implementation of an education programme in order to achieve (pre)determined results. It is not about intervention on students, but it is an experience of relationship where each one constructs their own story (Molina, Blanco & Arbiol, 2016). In short, curriculum is made through experiences that are lived in relation and, therefore, we could say that education is an act of relationship (Piussi, 2006). In this way, education does not require that teachers have the most appropriate knowledge and programme for every situation; the educational experience is unpredictable and ineffable, we cannot anticipate or face it completely (Van Manen, 2015). Thus, teaching requires becoming aware of how we build relationships and how we see the other person (Contreras, 2002).
Keywords: Profesores - Formación profesional; Educational relationship; Professional knowledge; Listening; Thoughtfulness; Curriculum making; Phenomenology